2020
DOI: 10.38157/society_sustainability.v2i3.157
|View full text |Cite
|
Sign up to set email alerts
|

Career Trajectories of the Female Faculties in the Private Universities of Bangladesh

Abstract: The education sector is considered as one of the suitable areas that facilitate women to pursue a prestigious career. Recently, along with public universities, private universities are significantly contributing to higher education in Bangladesh. Female faculties are building their careers in private universities. In university-level education, a faculty member plays a significant role in bringing out the talent hidden among the students and grooms them up for a future career. This study aims to trace the sati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Second, Bangladeshi gendered academia reflects larger temporal landscapes that shape WLB among women faculty, where official WLB policies or institutional practices are absent. 4 Amid the absence of official WLB policies and practices, like other Global South contexts, Bangladeshi women rely on informal practices of temporal flexibility to address their WLB needs (Hossain & Rokis, 2014 ; Tabassum & Rahman, 2020 ). Among the 15,571 academic members in Bangladesh, only 4,472 are women (Abbas, 2017 ).…”
Section: Bangladesh Gender and Academic Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, Bangladeshi gendered academia reflects larger temporal landscapes that shape WLB among women faculty, where official WLB policies or institutional practices are absent. 4 Amid the absence of official WLB policies and practices, like other Global South contexts, Bangladeshi women rely on informal practices of temporal flexibility to address their WLB needs (Hossain & Rokis, 2014 ; Tabassum & Rahman, 2020 ). Among the 15,571 academic members in Bangladesh, only 4,472 are women (Abbas, 2017 ).…”
Section: Bangladesh Gender and Academic Workmentioning
confidence: 99%
“…Furthermore, most women faculty in the Bangladeshi HE sector mirror the broader SA HE sector, which draws faculty from upper- or middle-class families (Hossain & Rokis, 2014 ; Morley & Crossouard, 2016 ). While the number of women entering the academic profession grew recently (Alam et al, 2005 ; Tabassum & Rahman, 2020 ), one major reason Bangladeshi women join academia is to gain temporal autonomy (i.e. flexible schedule) to meet family needs (Hossain & Rokis, 2014 ; Tabassum & Rahman, 2020 ).…”
Section: Bangladesh Gender and Academic Workmentioning
confidence: 99%
See 1 more Smart Citation
“…A complex shomoyscape was also instigated by childcare, forcing faculty to engage in temporal agency (e.g., accommodating child’s temporal need), particularly among female academics. Like gendered academics elsewhere (Acker and Armenti, 2004; Conesa and González, 2018; Spurling, 2015; Ylijoki, 2013), recent studies on Bangladeshi academics demonstrated that female academics face significant barriers to career trajectories and work/life balance, given the gendered labor towards family and childcare (e.g., Tabassum and Rahman, 2020; Uddin et al, 2013). Neela, introduced earlier, pointed out how the burden of childcare fell mostly on mothers.…”
Section: Caring For Others: Shomoyscapes Relationality and Re/calibra...mentioning
confidence: 99%
“…Based on this definition, Ramana, Varaprabhakar, and Malyadri (2020) referred job satisfaction as an efficacious personal attitude toward the nature of work and roles they really fulfill. It is further considered as the degree to which an individual likes or enjoys his/her job (Zhang, Ahmad, and Cao, 2018;Tabassum and Rahman, 2020;Dewi and Riana, 2020). In the same way, Elom et al (2018) prescribed job satisfaction as a state that is reflected and influenced by an individual"s work experiences, present and future hopes.…”
Section: Job Attitudesmentioning
confidence: 99%